Rodents of Senegal and their role as intermediate hosts of Hydatigera spp. (Cestoda: Taeniidae) - (:unkn) unknown (My University, 2019)
The species of small mammals involved in the study are classified as ‘Least Concern’ by the International Union for Conservation of Nature Red List. Animals were treated in compliance with the guidelines of the American Veterinary Medical Association Council (https://www.avma.org/KB/Policies/Documents/euthanasia.pdf) and the Animals (Scientific Procedures) Act as implemented by the Home Office in Great Britain (https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/535574/working-with-wild-animals-160706.pdf). Trapping activities commenced after explicit approval from local authorities and land owners. Approval for live trapping and euthanasia of small mammals was obtained from the Clinical Research Ethical Review Board of the Royal Veterinary College, University of London (reference number: 2016 1505).
Keywords: African Research